Development of an inquiry-based biology student worksheet based on the identification of Solanaceae plant trichomes for high school students - Febriani, Dinta Rizqi Aulia; Widyadinata, Nanda; Putri, Salwa Rachmanda; Anggrella, Dita Purwinda (Jurnal Edukasi Biologi, 2026)
This study aims to develop an inquiry-based biology student worksheet that integrates research findings on identifying trichome variations in Solanaceae plants as a contextual learning resource. The study uses a Research and Development approach with the ADDIE model limited to the Development stage. The development stage includes drafting a student worksheet based on micrograph data from trichome observations, expert validation, and product revision. The study objects include chili, tomato, and eggplant leaves, which were observed under a light microscope at 100× magnification to identify the types and shapes of trichomes. The results of the study indicate the presence of non-glandular trichome variations, namely simple hairs with hooked ends on chili, simple needle-like hairs on tomatoes, and stellate-shaped trichomes on eggplant. These findings are integrated into the student worksheet during the problem analysis activity. Validation was carried out by two experts, covering content feasibility, presentation, language, and graphics, using a 1-4 Likert scale. The validation results after revision showed an average value of 3.54, which falls within a very feasible category. A student worksheet based on research into trichome variation was deemed conceptually feasible as an inquiry-based teaching material for biology. This study was limited to a feasibility test using expert judgment; further research is needed to assess the practicality and effectiveness of the student worksheet through classroom implementation.